COLLABORATORS OR TROUBLE-MAKERS? THE DUAL IDENTITY OF NGOS IN CHINESE RURAL GOVERNANCE - Lihe Lin, (PEOPLE: International Journal of Social Sciences, 2026)
This study investigates the dynamic tension between the dual identities of Non-Governmental Organizations (NGOs) as collaborators versus trouble-makers within the context of Chinese rural governance. By employing a qualitative single-case study of Organization X in Village Y, H Province of China, this research constructs an analytical framework of ‘Boundary-Crossing Governance’ to elucidate the survival logic and interaction mechanisms of NGOs within a state-led system. The findings reveal a structural conflict between the professional-community logic of NGOs, which prioritizes long-term endogenous development, and the bureaucratic-administrative logic of local governments, driven by short-term stability and performance metrics. This institutional misalignment precipitates a legitimacy paradox when NGOs shift from service provision to rights advocacy. However, through functional boundary-crossing, NGOs impose reverse discipline on administrative power while navigating resistance from systemic inertia. To survive these dilemmas, Organization X demonstrates significant agency by deploying embedded strategies, including discursive isomorphism, gentle professionalism, and localized agent cultivation. The study concludes that such boundary-crossing constitutes a form of constructive friction. Rather than mere conflict, it serves as a critical mechanism for resilient boundary negotiation, allowing NGOs to carve out autonomous spaces within rigid institutional interstices and driving the incremental adaptation of China’s grassroots governance system.